Determination of Normal Liver Stiffness Range among Healthy Adults in Pakistan Using Shear Wave Elastography - Iftikhar, Ammara; Slehria, Atiq Ur Rehman; Saleem, Sultan; Awan, Aamir Aslam; Sadiq, Nosheen; Abbas, Waqas (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the reference values of liver stiffness in Pakistan using Shear Wave Elastography in subjects without liver disease, with a range of ages and BMI for both genders and to assess the influence of Hepatic Steatosis on liver stiffness values.Study Design: Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Radiology and Imaging, Rawalpindi Pakistan Aug 2018 to Sep 2019.Methodology: One hundred twenty-three subjects who underwent Shear Wave Elastography were enrolled. Measurements were taken from the right hepatic lobe, and the median kilopascal value of 10 measurements was taken as the representative value. The reference range of liver stiffness was calculated using upper and lower limits at 97.5 and 2.5 percentiles. The influence of hepatic steatosis age, body mass index, and gender on liver stiffness was also recorded.Results: The mean age of the subjects was 39.7±12.7 years with a male-to-female ratio of 1.4:1. The Mean liver stiffness value in healthy subjects was 4.90±0.64 kPa. No statistically significant difference was found in the values among various age groups (p=0.013) or the groups based on body mass index, except for the Obese-Group, whose values were considerably higher (p